DESIGNING A CHILDREN'S BOOK: TOMMY & DARKNESS TO OVERCOME FEAR OF SHADOWS (AGES 6-12) - Budi Darmo; Budi Sanjaya; Maylea Crysantie; Meiliana Tjiu; Matthew Agustino (Gorga : Jurnal Seni Rupa, 2024)
Children often feel fear of shadows in the dark, which frequently arises from imaginary creatures or their dreams. This fear disrupts their emotional development and affects their sleep routines, leading to issues like insomnia and anxiety. Addressing this issue through effective educational tools such as children's books is crucial, especially in Indonesia where children's interest in reading is still very low. This project aims to create a children's book titled "Tommy & Darkness," designed to help children aged 6-12 overcome their fear of shadows. The story follows a young boy named Tommy who learns to confront and understand his fear with the help of a friendly guide. The book employs the Design Thinking method from the Hasso-Plattner Institute of Design at Stanford to creatively and engagingly demonstrate that fear can be overcome through empathy and courage. This method emphasizes understanding the user's experience, encouraging children to relate to Tommy's journey. The book also aims to enhance children's emotional resilience in facing everyday challenges by showing that fear is a natural part of life and can be managed with the right mindset and support. Illustrated with vivid, colorful artwork, "Tommy & Darkness" captures children's attention and makes the story more engaging. Ultimately, this project seeks to foster a culture of reading in Indonesia while providing valuable lessons in emotional intelligence and resilience.